The Practice of Organizational Learning in Saudi Government Agencies - Albawardy, Faisal (The Arab Journal of Administration, 2020)
Study objectives: The main of the study is to identify the levels of organizational learning (OL) practice in Saudi government agencies. Moreover, the study also aims to determine whether there are in OL practices with respect to type of government agency and the demographic characteristics of civil service employees. Study Design: To achieve the study objectives, a questionnaire was developed based on the five learning dimensions of Strategic Learning Assessment Map Model (SLAM). Sample and Data: The study data were collected using a stratified random sampling from the study population which consists of all civil employees. A total of 528 questionnares returned from 600 questionnaires distributed to the sampled employees, giving 88% response rate. Result: The study results showed that the levels OL practices in Saudi government agencies were above moderate, and that individual learning was the most commonly practiced followed by group learning. Moreover, the study results showed that there were no significant differences in OL practices between government agencies, and also there were no signficant differences in OL practices with respect to demographic variables except with education. Conclusion: Based on the study results, a number of recommendations are made, the most important of which is to spread the learning culture and adopt policies and working procedures that support learning.